Tropical sand-bubblers heading north? First discovery of Scopimera curtelsona Shen, 1936 (Crustacea: Decapoda: Dotillidae) populations in Hong Kong: possible range expansion from Hainan, China - Hui, T. Y.; Wong, Kingsley J. H. (Zootaxa, 2019)
A sand-bubbler crab, Scopimera curtelsona Shen, 1936, previously known only from Hainan, China, is reported from Hong Kong. By searching past taxonomic records and examining local material, an increasing trend of S. curtelsona abundance was observed in comparison with another common sympatric dotillid, S. intermedia Balss, 1934, in Hong Kong since the early 2000s. This scenario is hypothesized to represent a northward range expansion of this tropical species from Hainan, China, by 500 km, coinciding with an increase in sea surface temperatures in Hong Kong, which are now at comparable levels with previous type locality temperatures. At a smaller scale, S. curtelsona was sympatric with two other dotillids: S. intermedia and Dotilla wichmanni De Man, 1892, on local sandflats, where the three species occupied different zones along the tidal gradient possibly due to the interaction between the variation in sediment characteristics and the crabs’ maxillipedal setation.